PREFERENCJE GOSPODARSTW DOMOWYCH I FIRM W ZAKRESIE ZAKUPU UBEZPIECZEŃ EMERYTALNYCH - Garczrczyk, Józef (Wydział Prawa i Administracji UAM, 1999)
During the researched period of the two last years: - in the opinion of persons managing household budgets the most important element of a retiring insurance is the credibility of a given insurance company and the amount of insurance premium (45 per cent). It is to be noted the growing importance of the premium amount and of the fact after how many years the pension should be available. Decreasing is the role of anti-inflationary measures and of the range of a given an insurance. Relatively least importance is still attached to a possibility of depositing an insurance in quality of a pawn in a bank. The same - for the manner of payment of retirement pension and for the frequency of insurance rate; - reliability of the insurer is being stressed more often by the professionals, persons from higher income households or those who claim their wealth level being high (55-65 per cent). The insurance premium amount is of bigger importance for the elderly, the less educated, the unpropertied and the pessimists; - percentage of those who are interested in possessing their private pension for retired has recently increased. However, relatively few persons do possess such an insurance (every tenth person) despite enough financial means for that aim. Relatively large group of the undecided has been separated (up to 15 per cent). A wish of possessing private retirement pension is thebigger the higher is education level of a person, the bigger are the wealth and income level of the household; average amount of the declared insurance rate is 118 PLN monthly. This sum increases together with education level and earnings of particular members of a household; interest the firms have in possessing a group insurance passed with an investment fund is now expressively bigger. An intention to start such a kind of insurance is being expressed by every third firm and almost every tenth is already in possession of it.
PREFERENCES OF HOUSEHOLDS AND FIRMS IN PURCHASING RETIRING INSURANCES